Impact of corona treatment on PLA film properties. (October 2016) - Rocca-Smith, Jeancarlo R.; Karbowiak, Thomas; Marcuzzo, Eva; Sensidoni, Alessandro; Piasente, Francesca; Champion, Dominique; Heinz, Olivier; Vitry, Pauline; Bourillot, Eric; Lesniewska, Eric; Debeaufort, Frédéric
Abstract: Different types of PLA films treated by corona are currently available in the market for coating or printing applications. However, data relative to its impact on PLA film properties are scarce and do not generally consider industrial scale production. The objective of this study was to assess the impact of corona treatment on the surface, structure and barrier properties of bi-oriented PLA films produced at industrial scale. Thus, a comparative study between corona treated (CT) and non-corona treated (NCT) PLA films was conducted. The surface of films was studied using Attenuated Total Reflectance Fourier Infrared Spectroscopy (ATR-FTIR), X-ray Photoelectron Spectroscopy (XPS), Atomic Force Microscopy (AFM) and goniometry measurements. The structure of films was analyzed with thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and uniaxial tensile analysis. The barrier properties of films to three gases (He, O2, CO2 ) were also determined. This study unambiguously revealed that corona treatment led to modifications in both surface and bulk of PLA films. In particular, surface analysis displayed the well-known capability of corona treatment to chemically and physically modify the surface of PLA films at the nanometer scale by increasing polarity and roughness. The structural analysis displayed a slight increase in the crystallinity degree and slight modifications in mechanical properties of films. This probably originated from temperature increase associated to corona treatment, which favored physical changes ( e.g. relaxation, crystallization) of a part of the bi-orientated PLA chains, and therefore highlights the importance of such an industrial step on the film properties for packaging applications. As a result of these modifications, the barrier properties of films to three gases (He, O2, CO2 ) are also slightly improved.